Multivariat Predict Sales Data Using the Recurrent Neural Network (RNN) Method - Ardriani, Ni Nengah Dita; Yastawil, Jamiin Al Yastawil; Erawati, Kadek Nonik; Yudi Antara, I Gede Made; Santiago, Gede Agus (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2024)
Sales is an activity or business selling a product or service. In this study, I took a case study on Kaggle. Sales problems at the company cause inventory to be very high or vice versa, causing a loss of sales because there are no items to sell. Inventory that is too high results in increased costs due to existing resources being inefficient. In the opposite condition, it will cause a product vacancy in the market. Using the Recurrent Neural Network (RNN) Algorithm, this study predicts sales. The data used is sales data in 2020 with the parameter Number of sales per day in the last four months. The results obtained through testing several training scenarios and testing the implementation of the algorithm, in this case, is the highest accuracy value of 96.92% in the network architecture of three input neuron layers, three hidden layer neurons, one output, division of training, and test data 70: 30, learning value rate of 0.9 and a maximum of 9000000 epochs